Research of Tooth Profile Construction Mechanism of Cross Shaft Line Gear - He Enyi (Jixie chuandong)
During the meshing process of line gear,the normal side gap affects the transition from the positive to the reverse. Based on the space curve meshing theory,the spiral surface gears which can suit the positive and reverse transmission is researched. Taking the spiral line as the center line,the curved surface equation is studied,the driving surface is constructed. The positive and negative switching contact lines on the driven surface are analyzed. According to the positive and negative transfer line,the rectangular section is constructed,which can include the circular cross section of the driving surface. The curved surface equation is studied for constructing the driven surface. The kinematic performance of this kind of gear is studied. The results show that the gear pairs constructed by this method can fully transition without the large normal side gap,and meet the needs of the transmission.